Prevalence and risk factors of cardiovascular diseases among Bangladeshi adults: Findings from a cross-sectional study - Khanam, Fouzia; Hossain, Md. Belal; Mistry, Sabuj Kanti; Afsana, Kaosar; Rahman, Mahfuzar (Atlantis Press, 2022)
This article was published in Journal of Epidemiology and Global Health [ © 2019 Atlantis Press International B.V.] and the definite version is available at: https://doi.org/10.2991/jegh.k.190531.001. The Journal's website is at: https://www.atlantis-press.com/journals/jegh/125913526